Neuropilin-1 as Therapeutic Target for Malignant Melanoma - Graziani, Grazia; Lacal, Pedro M. (Frontiers in Oncology, 2015)
Neuropilin-1 (NRP-1) is a transmembrane glycoprotein that acts as a co-receptor for various members of the VEGF family. Its ability to bind or modulate the activity of a number of other extracellular ligands, such as class 3 semaphorins, TGF-β, HGF, FGF and PDGF, has suggested the involvement of NRP-1 in a variety of physiological and pathological processes. Actually, this co-receptor has been implicated in axon guidance, angiogenesis and immune responses. NRP-1 is also expressed in a variety of cancers (prostate, lung, pancreatic or colon carcinoma, melanoma, astrocytoma, glioblastoma and neuroblastoma), suggesting a critical role in tumor progression. Moreover, a growing amount of evidence indicates that NRP-1 might display important functions independently of other VEGF receptors. In particular, in the absence of VEGFR-1/2, NRP-1 promotes melanoma invasiveness, through the activation of selected integrins, by stimulating VEGF-A and metalloproteinases secretion and modulating specific signal transduction pathways. This review is focused on the role of NRP-1 in melanoma aggressiveness and on the evidence supporting its use as target of therapies for metastatic melanoma.